Social support from fellow people living with HIV/ AIDS (PLWHA) and adherence to ARV treatment among PLWHA in Indonesia: Literature review - Pujaannicha, Pujaannicha; Widiana, Herlina Siwi (Universitas Ahmad Dahlan, 2024)
Low adherence to ARV treatment in people living with HIV/AIDS (PLWHA) can lead to drug resistance, increased transmission, and worsen the condition of PLWHA due to insufficient HIV suppression in the body, ultimately increasing HIV-related mortality. Therefore, adherence to ARV treatment is crucial. This study aims to explore the social support among PLWHA and its impact on ARV treatment adherence. The databases used include Google Scholar, ScienceDirect, ResearchGate, Elsevier, and PubMed, based on articles published in the last 8 years, primary research articles, and written in Indonesian or English, with the research conducted in Indonesia. The literature review of 14 articles indicates that social support among PLWHA can significantly affect adherence to ARV treatment in Indonesia. In conclusion, PLWHA is more likely to adhere to ARV treatment with adequate social support from fellow PLWHA.